Cumplimiento De Funciones En El Comercial Escobar De Vinces - Gavilanez Moposita, Veronica Alexandra (2017)
The commercial Escobar de Vinces is a private company owned by Mr. Ángel Escobar Maliza and Mrs. Emma Apunte Aguirre entity that through the years has been evolving in sales where at the beginning they started with a store of supplies to become a company of high level of positioning with a feasible performance, leading to source of work for society has the necessary departments and a welcoming environment, areas classified according to their nature, high technology equipment, updated programs and a staff with knowledge in their areas, who works every day to do his job better. The manager to measure performance uses two types of parameters that are the margin of error and the optimization of time, based on this the manager performs a performance evaluation to know their behaviors, potential development and their labor participation, this is done monthly using the technique of interview and reports, results that have not been satisfactory.